Innovativeness Level Vs Cooperation between Companies in Poland - Agnieszka PESZKO (Communications of International Proceedings, 2021)
The aim of this paper is to analyse and assess the cooperation of Polish enterprises in the field of innovative activities. In order to achieve the goal of this publication, the following questions were asked: What does it mean to be an innovative enterprise? Are Polish enterprises innovative? Do Polish companies cooperate in innovative efforts? What entities do Polish enterprises cooperate with? Are entrepreneurs satisfied with the cooperation? The study was based on the available literature as well as the author’s own analyses based on the data provided by the Polish Statistical Office, Eurostat and Polish Agency for Enterprise Development.
Keywords: Cooperation; Innovativeness; Polish Enterprises.